Structure of hypernucleus 7_ΛLi within microscopic three-cluster model - Kalzhigitov, Nursultan; Amangeldinova, Sabina; Vasilevsky, Victor (My University, 2025)
The structure of bound and resonance states of the hypernucleus 7_ΛLi is studied within a three-cluster model. This nucleus is considered a three-cluster structure consisting of 4He, a deuteron, and a lambda hyperon. The chosen three-cluster configuration allows us to describe more accurately the structure of hypernucleus 7_ΛLi and the dynamics of different processes that involve interactions of lightest nuclei and hypernuclei. The main goal of the present investigations is to find resonance states in the three-cluster continuum of 7_ΛLi and determine their nature. A set of narrow resonance states is detected at the energy range 0 < E <= 2 MeV above the three-cluster threshold 4He+d+Λ.
Keywords: Cluster model; resonance states; three-cluster model; hypernuclei